Om skoluniformen i skolan och scoutskjortan på fritiden: Några jämförande iakttagelser - Westberg, Anna (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2005)
The Scout Movement has 38 million members all over the world, most of which wear scout uniforms. In Sweden there are five scout associations. The aim of this article was to study how the uniform is used in one of them. Twenty-eight members of The Swedish Guide and Scout Association were interviewed. The informants were between nine and 54 years old, half of them were women and half of them were men, and they came from three different scout groups in different parts of Sweden. The study has been carried out within the field of child and youth science.